Combination therapy with andrographolide and d-penicillamine enhanced therapeutic advantage over monotherapy with d-penicillamine in attenuating fibrogenic response and cell death in the periportal zone of liver in rats during copper toxicosis - Roy, Dijendra Nath; Sen, Gargi; Chowdhury, Kaustav Dutta; Biswas, Tuli (Toxicology and applied pharmacology, 2011)
Long treatment regime with d-penicillamine is needed before it can exert clinically meaningful benefits in the treatment of copper toxicosis. The consequence of long-term d-penicillamine treatment is associated with numerous side effects. The limitations of d-penicillamine monotherapy prompted us to search for more effective treatment strategies that could decrease the duration of d-penicillamine therapy. The present study was designed to evaluate the therapeutic potential of d-penicillamine in combination with another hepatoprotective drug, andrographolide in treatment of copper toxicosis in rats. d-penicillamine treatment led to the excretion of copper through urine. Addition of andrographolide to d-penicillamine regime appeared to increase protection of liver by increasing the biliary excretion of copper and reduction in cholestatic injury. The early removal of the causative agent copper during combination treatment was the most effective therapeutic intervention that contributed to the early rectification of fibrosis in liver. Combination treatment reduced Kupffer cells accumulation and TNFα production in liver of copper exposed rats. In particular, andrographolide mediated the anti-inflammatory effect by inhibiting the cytokine production. However, another possible mechanism of cytoprotection of andrographolide was decreasing mitochondrial production of superoxide anions that resulted in better restoration of mitochondrial dysfunction during combination therapy than monotherapy. Furthermore, ROS inhibition by combination regimen resulted in significant decline in activation of caspase cascade. Inhibition of caspases attenuated apoptosis of hepatocytes, induced by chronic copper exposure. In summary, this study suggested that added benefit of combination treatment over use of either agent alone in alleviating the hepatotoxicity and fibrosis associated with copper toxicosis.